Development of a superconducting magnetic system of a plasma mass-separator - Ilichova, V.О.; Druj, O.S.; Yuferov, V.B.; Sharyi, S.V. (Вопросы атомной науки и техники, 2006)
The paper presents the design and parameters of a superconducting magnetic system of a mass-separator with a
maximum magnetic field value of about 5 and 3 T in the separation area. The magnetic system is designed for a NbTi
copper-stabilized superconductor; for current leads HTSC is used. The stored energy is 6 MJ. Heat inputs to the
surfaces with T of 4.5 and 40 K are equal to 1 and 50 W, respectively. Представлены конструкция и параметры сверхпроводящей магнитной системы сепаратора изотопов с
максимальной величиной магнитного поля ~5 и 3 Тл в области сепарации. Магнитная система расcчитана на
Nb-Ti сверхпроводник, стабилизированный медью; для токовводов используется ВТСП. Запасенная энергия
составляет ~ 6 МДж. Теплоподводы к поверхностям с температурой 4.5 и 40 К равны 1 и 50 Вт Представлені конструкція та параметри надпровідної магнітної системи сепаратора ізотопів з
максимальним значенням магнітного поля біля ~5 та 3 Тл в області сепарації. Магнітна система розрахована
на Nb-Ti надпровідник, стабілізований міддю; для струмовводів використовується ВТНП. Запасена енергія
становить ~ 6 МДж. Теплопідводи до поверхонь з температурою 4.5 та 40К становлять 1 та 50 Вт.